Incorporation of Ti as a Pyramidal Framework Site in the Mono‐Layered MCM‐56 Zeolite and its Oxidation Activity. Issue 1 (21st August 2018) - Korzeniowska, Aleksandra; Grzybek, Justyna; Roth, Wieslaw J.; Kowalczyk, Andrzej; Michorczyk, Piotr; Čejka, Jiři; Přech, Jan; Gil, Barbara
Abstract: MWW zeolite MCM‐56 with Al atoms on the surface was functionalized with Ti to produce pyramidal TiOH groups. This was carried out by removal of Al with nitric acid, calcination and treatment with titanium diisopropoxide bis(acetylacetonate) (Ti(acac)2 (i‐propoxide)2, Ti(acac)2 OiPr2 ). Up to 0.7 % Ti was introduced. Using UV‐Vis spectroscopy three types of Ti moieties were identified in the uncalcined materials – tetrahedral in the framework, 5/6‐coordinated Ti on the surface, presumably in the vacated pyramidal sites, and oxide‐like clusters. The presence of TiOH on the surface was indicated by in situ measurement of UV‐Vis spectra during calcination. It showed the band at 290 nm, which disappeared at 500 °C, perhaps due to condensation with silanols. Catalytic oxidation tests were carried out with three samples containing 0.13, 0.36, and 0.70 % Ti and methyl phenyl sulfide and cis‐cyclooctene as model reactants. The study confirmed potential of the TiOH moieties in oxidation catalysis although their final form is not certain. Future studies will include increasing Ti content to enhance catalytic activity and better detection of this type of the Ti site. Abstract : Modern pyramids ! MWW structure with high Al content on the surface can produce TiOH as non‐defect oxidation centers. Up to 0.7% Ti was introduced. High catalytic activity was observed in model oxidation of methyl phenyl sulfide and cis‐cyclooctene.